2020
DOI: 10.1101/2020.08.06.20169797
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The effect of school closures and reopening strategies on COVID-19 infection dynamics in the San Francisco Bay Area: a cross-sectional survey and modeling analysis

Abstract: Background Large-scale school closures have been implemented worldwide to curb the spread of COVID-19. However, the impact of school closures and re-opening on epidemic dynamics remains unclear. Methods We simulated COVID-19 transmission dynamics using an individual-based stochastic model, incorporating social-contact data of school-aged children during shelter-in-place orders derived from Bay Area (California) household surveys. We simulated transmission under observed conditions and counterfactual interve… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
45
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(63 citation statements)
references
References 77 publications
16
45
1
Order By: Relevance
“…The results show similar trends for the Baseline, 80% in-person learning, 40% 2-day and alternating week, and offsite school scenarios with Fewer Open Workplaces and More Open Workplaces assumptions for both regional and national simulations. All the partial onsite learning scenarios delay the epidemic peak and flatten the curve for Fewer Open Workplaces, which is consistent with previous studies on school closures [13][14][15][16] (Figure 2, 3). However, for More Open Workplaces, the peak for most scenarios is spread around three weeks regardless of school reopening scenario and the impact of hybrid school reopenings is reduced.…”
Section: Overall Regional and National Impactssupporting
confidence: 91%
See 1 more Smart Citation
“…The results show similar trends for the Baseline, 80% in-person learning, 40% 2-day and alternating week, and offsite school scenarios with Fewer Open Workplaces and More Open Workplaces assumptions for both regional and national simulations. All the partial onsite learning scenarios delay the epidemic peak and flatten the curve for Fewer Open Workplaces, which is consistent with previous studies on school closures [13][14][15][16] (Figure 2, 3). However, for More Open Workplaces, the peak for most scenarios is spread around three weeks regardless of school reopening scenario and the impact of hybrid school reopenings is reduced.…”
Section: Overall Regional and National Impactssupporting
confidence: 91%
“…The copyright holder for this preprint this version posted October 13, 2020. ; https://doi.org/10.1101/2020.10.09.20208876 doi: medRxiv preprint the spread of COVID-19 [15]. In addition, hybrid approaches to learning, such as capping the inperson classroom size, may be effective in reducing transmission [14,16] and provide a balance approach between supporting education while limiting the spread of COVID-19.…”
Section: Introductionmentioning
confidence: 99%
“…This is due in part to our assumption that asymptomatic and 11 symptomatic infections contribute similarly to transmission [26,67,37,36,68], and in part to our model's ability to capture chains of transmission within schools and extending out into the community. Our study echoes several modeling studies in emphasizing the importance of reducing school capacity to impede transmission [61,62,63,64,72]. Taking all this evidence together, those deciding on strategies to safely reopen schools should strongly consider operating at reduced capacity and strictly enforcing face-mask adherence.…”
supporting
confidence: 71%
“…Whereas a previous optimal control analysis of pandemic influenza (Shim 2013) suggested that age-specific optimal controls were all relatively similar, recent work on COVID-19 (Richard et al 2020;Gondim and Machado 2020) suggests that optimal controls should be higher for older age-groups due to their higher risk of severe disease and death. Inclusion of age structure is important for other reasons too, such as realistically capturing transmission dynamics (Britton et al 2020) and accounting for age-specific interventions, such as school closures (Head et al 2020). Additional limitations that affect our model's suitability for making future predictions include its deterministic nature and the rudimentary calibration procedure that we performed, which was sufficient to provide a basis for qualitative analyses but that would need refinement for application of our model to inference or forecasting.…”
Section: Figmentioning
confidence: 99%